Antimicrobial activity of a new series of Bis(isoxazoline),Bis(isoxazole)and their derivatives - Gajbhiye, Jayant M.; Chopade, A. U. (International Journal of Chemical and Physical Sciences, 2014)
A series of 1,1-bis [2-hydroxy-3-(5’-aryl-isoxazoline-3-yl)-5-methyl phenyl] methane and 1,1-bis [2-hydroxy-3-(5’-aryl-isoxazol-3-yl)-5-methyl phenyl] methane derivatives were evaluated for their antimicrobial activity against some selected pathogenic micro-organisms such as Gram-positive bacteria, Staphylococcus aureus, Citrobacter frundii, Bacillus megatherium and Gram-negative bacteria Staphyloccus aureus, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Enterobacter aerogenes, Salmonella typhi, Proteus vulgaris.

Determination of optimum values of descriptors to set filters for synthetic tri-pyrrole derivatives (prodiginines) against multi drug resistant strain of plasmodium falciparum - Masand, Vijay H.; Mahajan, Devidas T.; Pourbasheer, Eslam; Hadda, Taibi Ben; Chauhan, Harsh; Gajbhiye, Jayant M.; Alafeefy, A. M. (Current Research in Drug Discovery, 2014)
Abstract: In the present study, we have carried out extensive non-linear Quantitative-Structure Activity Relationship (QSAR) analysis to correlate in vitro anti-malarial activity against multi drug resistant strain of Plasmodium falciparum. Forty-three synthetic prodiginines with different structural features were used for their potential antimalarial activity. Linear, bilinear, biexponential and parabolic equations were developed. These equations were compared to determine the optimum values of descriptors for very useful and easily interpretable descriptors. The optimum values of these descriptors could be helpful in finding and optimizing a good lead compound. Obtained correlations reveal that various factors like lipophilicity, molecular weight and number of bonds have non-linear relation with the anti-malarial activity. Keywords: Prodiginines, Anti-Malarial Activity, Optimum/Desirability Values, Hybrid Inverse-QSAR

Facile esterification of carboxylic acid using amide functionalized benzimidazolium dicationic ionic liquids - Muskawar, Prashant Narayan; Thenmozhi, K.; Gajbhiye, Jayant M.; Bhagat, Pundlik Rambhau (Applied Catalysis A-General, 2014)
Herein, we report the synthesis of a new series of amide functionalized dicationic benzimidazolium based ionic liquids (DBimILs) and appraised their efficacy towards perceptive esterification of carboxylic acids with alkyl/allyl/aryl halides in presence of triethylamine. The amide groups present in this new series of DBimILs are expected to form hydrogen bonding with the carboxylic acids and this could facilitate the esterification reactions under mild conditions devoid of any added catalyst or organic solvent. The plausible mechanism for the enhanced catalytic activity in presence of this new series of ILs has been proposed. The corresponding alkyl/allyl/aryl esters isolated from this reaction were of high purity after simple extraction, which wipe out the necessity for further purification. This protocol addresses clean methodology and the efficient recyclability as well as reusability of the catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Benzimidazolium; Dicationic ionic liquids; Esterification; Homogenous catalysis

Preparation of pyrazole carboxylic acid analogues as anti-mycobacterial drug candidates - Gajbhiye, Jayant M. (WO2014174457 A1, 2014)
The present invention relates to the pyrazole carboxylic acid analogues of Formula (1) or stereoisomers, or esters or pharmaceutically acceptable salts thereof, as potent anti- mycobacterial agents. Formula Further it discloses the pharmaceutical composition comprising compounds of Formula-I for the treatment of mycobacterial infections.

Advances and recent applications in LC-MS and HPLC - Azharuddin, Quazi Syed; Mahajan, Devidas T.; Masand, Vijay H.; Alafeefy, Ahmed M.; Gajbhiye, Jayant M.; El-Sayed, Nahed Nasser Eid; Wajid, Abdul; Mohammad, Noor (Elsevier, 2015)
Advances and Recent Applications in LC-MS and HPLC presents the most recent developments in liquid chromatography and mass spectrometry techniques. The book’s content reaches across a range of disciplines and cites several case studies to effectively capture the advanced applications that make LC-MS and HPLC multifunctional and exacting techniques. Liquid chromatography and mass spectrometry systems generate chromatograms of column peaks and can provide molecular weights of separated materials and their solvent complexes. However, while these systems can provide structural information to confirm the identity of the compounds separated, the process is very expensive. This book provides identification of simple compounds resulting from fragmentation studies and their subsequent results, offering the reader access to information unavailable elsewhere and allowing researchers to avoid incurring the costs associated with obtaining the hands-on results that LC-MS systems generate. Applicable to chemical analysis, bioanalysis, and medicinal chemistry, as well as pharmaceutical science, synthetic chemistry, and industrial chemistry, Advances and Recent Applications in LC-MS and HPLC is a multidisciplinary reference that arms scientists with the latest research. Detailed case studies enable researchers to make the book's concepts immediately implementable.

Ammonium persulfate activated DMSO as a one-carbon synthon for the synthesis of methylenebisamides and other applications - Mahajan, Pankaj S.; Tanpure, Subhash D.; More, Namita A.; Gajbhiye, Jayant M.; Mhaske, Santosh B. (RSC Advances, 2015)
Activation of DMSO to work as an economical and environmentally benign one-carbon synthon has been achieved by using a bench-top reagent ammonium persulfate for general and efficient access to symmetrical methylenebisamides from primary amides. This methodology was used to achieve a three-component Mannich reaction using acetophenone, saccharin and DMSO to furnish a beta-amino ketone. It also provided a metal-free synthesis of thiadiazole and bis(phenyl)methane. Effectively, this method uses DMSO as a safer surrogate to formaldehyde. A mechanism for methylenebisamide formation involving radical intermediates has been proposed based on mechanistic studies.

Analysis of pantaprazole na monohydrate and sesquihydrate by powder x-ray diffraction (PXRD) - Mahajan, Devidas T.; Mohmad, Noor; Raut, D. M.; Gajbhiye, Jayant M. (Journal of Medicinal Chemistry and Drug Discovery, 2015)
Pantaprazole Na monohydrate and sesquihydrate were characterized by PXRD.significant difference in the diffraction patterns of Pantaprazole Na hydrates. The sesquihydrate contains all the diffraction peaks of monohydrate in addition to peaks.

Virtual screening techniques to probe the antimalarial activity of some traditionally used phytochemicals - Shibi, Indira G.; Aswathy, Lilly; Jisha, Radhakrishnan S.; Masand, Vijay H.; Gajbhiye, Jayant M. (Combinatorial Chemistry & High Throughput Screening, 2016)
Malaria parasites show resistance to most of the antimalarial drugs and hence developing antimalarials which can act on multitargets rather than a single target will be a promising strategy of drug design. Here we report a new approach by which virtual screening of 292 unique phytochemicals present in 72 traditionally important herbs is used for finding out inhibitors of plasmepsin-2 and falcipain-2 for antimalarial activity against P. falciparum. Initial screenings of the selected molecules by Random Forest algorithm model of Weka using the bioassay datasets AID 504850 and AID 2302 screened 120 out of the total 292 phytochemicals to be active against the targets. Toxtree scan cautioned 21 compounds to be either carcinogenic or mutagenic and were thus removed for further analysis. Out of the remaining 99 compounds, only 46 compounds offered drug-likeness as per the `rule of five' criteria. Out of ten antimalarial drug targets, only two target proteins such as 3BPF and 3PNR of falcipain-2 and 1PFZ and 2BJU of plasmepsin-2 are selected as targets. The potential binding of the selected 46 compounds to the active sites of these four targets was analyzed using MOE software. The docked conformations and the interactions with the binding pocket residues of the target proteins were understood by `Ligplot' analysis. It has been found that 8 compounds are dual inhibitors of falcipain-2 and plasmepsin-2, with the best binding energies. Compound 117 (6aR, 12aS)-12a-Hydroxy-9-methoxy-2,3-dimethylenedioxy-8-prenylrotenone (Usaratenoid C) present in the plant Millettia usaramensis showed maximum molecular docking score.
Keywords: ADME; malaria; Molecular docking; molecular operating environment; Plasmodium falciparum; virtual screening; weka

Computational strategies to explore antimalarial thiazine alkaloid lead compounds based on an australian marine sponge plakortis lita - Lilly, Aswathy; Jisha, R. S.; Masand, Vijay H.; Gajbhiye, Jayant M.; Shibi, Indira G. (Journal of biomolecular Structure & Dynamics, 2017)
In this work, an attempt was made to propose new leads based on the natural scaffold Thiaplakortone-A active against malaria. The 2D QSAR studies suggested that three descriptors correlate with the anti-malarial activity with an R2 value of 0.814. Robustness, reliability and predictive power of the model were tested by internal validation, external validation, Y-scrambling and Applicability domain analysis. HQSAR studies were carried out as an additional tool to find the sub-structural fingerprints. The CoMFA and CoMSIA models gave Q2 values of 0.813 and 0.647, and R2ncv values of 0.994 and 0.984, respectively. Using the 2D-QSAR equation, the activity values of the seven modified compounds were calculated and it was found that three molecules showed good anti-malarial activity. Molecular docking of the 42 Thiaplakortone-A derivatives with P. falciparum calcium-dependent protein kinase 1 (PfCDPK1) was carried out to find out protein-ligand interactions. Data mining of the bioassay dataset AID: 504850 using the classifier based on Random Forest (RF) of Weka suggested that all of the eight molecules selected and three out of the seven virtual molecules were anti-malarial active. Both the virtual molecules and drug molecules were docked with CYP3A4, indicating that the virtual molecules could metabolize easily. Toxicity studies using Osiris shows that three molecules showed no toxic characters.

Hybrids of thienopyrimidinones and thiouracils as anti-tubercular agents: SAR and docking studies - Pisal, Mahesh M.; Nawale, Laxman U.; Patil, Manoj; Bhansali, Sujit G.; Gajbhiye, Jayant M.; Sarkar, Dhiman; Chavan, Subhash P.; Borate, Hanumant B. (European Journal of Medicinal Chemistry, 2017)
A number of hybrid molecules containing thienopyrimidinones and thiouracil moieties were designed, synthesized and tested against Mycobacterium tuberculosis H37Ra wherein it was observed that the compounds 11-1514 exhibited antitubercular activity in vitro (MIC 7.6–19.1 μg/ml, 12–35 μM) against dormant stage while compound 15 exhibited antitubercular activity in vitro against dormant (MIC 23.4 μg/ml, 41 μM) as well as active (MIC 25.4 μg/ml, 45 μM) stage. Structural modifications of compound 15 were carried out to study the structure-activity relationship and it was observed that compound 18 exhibited antitubercular activity comparable to compound 15. Cytotoxicity studies revealed that these molecules were non-toxic. The docking study of compound 15 showed that there was binding with the active site of mycobacterial pantothenate synthetase. Further docking studies led to the synthesis of the compounds 16 and 17 and the antitubercular activity screening results showed that these compounds have significant antitubercular activity. The compounds 15-18 (MIC 11–29 μg/ml, 19–51 μM) can be used as starting points for further optimization. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures and the present results will be very useful in the development of a new class of antimycobacterial agents.

Solvent-free synthesis of thiobarbituric acids using amberlyst-15 as a green catalyst - Dhonde, Madhukar G.; Gajbhiye, Jayant M.; Katiya, Manish M. (Current Green Chemistry, 2017)

cRGD functionalized nanocarriers for targeted delivery of bioactives - Gajbhiye, Kavita Rai; Gajbhiye, Virendra; Siddiqui, Imtiaz A.; Gajbhiye, Jayant M. (Journal of Drug Targeting, 2019)
The integrins αvβ3 play a very imperative role in angiogenesis and are overexpressed in endothelial cells of the tumor. Recent years have witnessed huge exploration in the field of αvβ3 integrin-mediated bioactive targeting for treatment of cancer. In these studies, the cRGD peptide has been employed extensively owing to their binding capacity to the αvβ3 integrin. Principally, RGD-based approaches comprise of antagonist molecules of the RGD sequence, drug-RGD conjugates, and most importantly tethering of the nanocarrier surface with the RGD peptide as targeting ligand. Targeting tumor vasculature or cells via cRGD conjugated nanocarriers have emerged as a promising technique for delivering chemotherapeutic drugs and imaging agents for cancer theranostics. In this review, primary emphasis has been given on the application of cRGD-anchored nanocarriers for targeted delivery of drugs, imaging agents, etc. for tumor therapy.
Keywords: alpha(v)beta(3) integrin receptors; cancer; cRGD; nanocarriers; targeting

Novel fatty alkene from marine bacteria: a thermo stable biosurfactant and its applications - Ram, Hari; Sahu, Amit Kumar; Said, Madhukar S.; Banpurkar, Arun G.; Gajbhiye, Jayant M.; Dastager, Syed G. (Journal of Hazardous Materials, 2019)
In this study, a novel thermo stable biosurfactants, 1-Pentanonacontene (C95H190) a fatty alkene and 3-Hydroxy16-methylheptadecanoic acid (C18H36O3) were isolated from a marine isolate SGD-AC-13. Biosurfactants were produced using 1% yeast extract in tap water as production medium at 24 h in flask and 12 h in bioreactor. Using 16S rRNA gene sequence (1515 bp) and BCL card (bioMerieux VITEK (R)), strain was identified as Bacillus sp. Crude biosurfactant reduced the surface tension of distilled water to 31.32 +/- 0.93 mN/m with CMC value of 0.3 mg/ml. Cell free supernatant showed excellent emulsification and oil displacement activity with stability up to 160 degrees C, pH 6-12 and 50 g/L NaCl conc. Biosurfactants were characterized using FTIR, TLC, HPLC LC-MS and NMR spectroscopy. Cell free supernatant reduced the contact angle of distilled water droplet from 117 degrees to 52.28 degrees and of 2% pesticide from 78.77 degrees to 73.42 degrees while 750 mu g/ml of crude biosurfactant reduced from 66.06 degrees to 56.33 degrees for 2% pesticide and recovered 35% ULO and 12% HWCO from the contaminated sand. To our best of knowledge, this is the first report of thermo stable fatty alkene as a biosurfactant and is structurally different from previously reported, with having potential application in agriculture, oil recovery and bioremediation.
Keywords: Bioremediation; Biosurfactants; Fatty alkene; Thermo stability; Wettability

Regioselective one-pot synthesis of 3-fluoro-imidazo[1,2-a]pyridines from styrene - Said, Madhukar S.; Mishra, Ankita; Pandole, Satish; Nayak, Rashmi A.; Kumar, Pradeep; Gajbhiye, Jayant M. (Asian Journal of Organic Chemistry, 2019)
A one-pot synthesis of C-3 fluorinated imidazopyridines (F-IMPY) is reported under the additive-free conditions from commercially available styrene and 1-fluoropyridinium tetrafluoroborate as a fluorine source. The substrate styrene undergoes keto-bromination/condensation/fluorination transformation in three sequential steps to furnish F-IMPY. This one-pot synthesis method exhibits broad substrate scope and good functional group tolerance with a good yield (up to 82%).
Keywords: fluorination; imidazopyridines (F-IMPY); One-pot synthesis

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Metal-free, Tf2NH-catalyzed 1, 6-conjugate addition of imidazopyridine to para-quinone methides: easy access to C3-functionalized triarylmethane imidazopyridine - Khonde, Nilesh S.; Said, Madhukar S.; Sabane, Jagjivan K.; Gajbhiye, Jayant M.; Kumar, Pradeep (Tetrahedron, 2021)
An inexpensive and commercially available Tf2NH-catalyzed 1,6-conjugate addition of imidazopyridine (IMPY) heterocycles to para-quinone methides (p-QMs) is reported. The present transformation provides a diverse class of C3-functionalized triarylmethanes heterocyclic derivatives of imidazopyridine. These metal-free transformations provided a very broad substrate scope of conjugate addition product with a high yield up to 97% within a short duration. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Conjugate addition; Bronsted acid; C3-functionalization; Imidazopyridine; para-Quinone methide

Novel 3-fluoro-4-morpholinoaniline derivatives: synthesis and assessment of anti-cancer activity in breast cancer cells - More, Namita A.; Jadhao, Nitin L.; Meshram, Rohan J.; Tambe, Prajakta; Salve, Rajesh A.; Sabane, Jagjivan K.; Sawant, Sanskruti N.; Gajbhiye, Virendra; Gajbhiye, Jayant M. (Journal of Molecular Structure, 2022)
Heterocyclic morpholine compounds are well-known for their anti-cancer activity. In this study, novel morpholine and its sulfonamide derivatives were designed and synthesized as potential anti-tumor agents. The new compounds were obtained from amine derivatives via nucleophilic addition reactions, providing the desired products in 70 to 90% yield. The docking analysis was performed for all thirty-one compounds. Out of them, we represent the docking poses for compounds NAM-5 and NAM-7 as representatives. After docking analysis, compounds NAM-5 and NAM- 7 were tested for in vitro antitumor activity against breast cancer cell lines (MCF-7 and MDA-MB-231) and healthy mouse embryonic fibroblast cell line (3T3L-1). Amongst these, sulfonamide group-containing compound NAM-5 showed significant anti-proliferative activity with IC50 of 1.811 mu M and 2.143 mu M for MCF-7 and MDA-MB-231 cells, respectively. On the other hand, NAM-7 showed good anti-proliferative activity against MCF-7 (IC50 1.883 mu M) but slightly lower activity against MDA-MB-231 cells (IC50 4.688 mu M). The activity of both the compound was also tested on 3T3L-1 Cell line which showed activity similar to clinically approved anti-cancer drug doxorubicin (DOX). The cell death analysis by flow-cytometry confirmed apoptosis mediated cell death in 3T3L-1, MCF-7 and MDA-MB-231 cells when treated with the NAM-5 and NAM-7, respectively. The results demonstrated that the synthesized sulfonamide derivatives have significant potential as anti-cancer agents and have a substantial importance in cancer therapeutics with favourable safety profile. Structural analysis of docked poses of sulfonamide derivatives attempts to shed light on the structural basis of sulfonamide derivatives based anti-cancer effect. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anticancer activity; Apoptosis; Breast cancer; Heterocyclic compounds; Morpholine; Sulfonamide

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides

Synthesis of pyrazole and 1,3,4-oxadiazole derivatives of pharmaceutical potential - Kadam, Mayur; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Prospects in Pharmaceutical Sciences, 2024)
Heterocyclic compounds are important molecules that serve as scaffolds or linkers for the core structure of numerous drug substances. In particular, pyrazole and 1,3,4-oxadiazole are compounds of great interest due to their comprehensive biological activities and interesting structural features. Here, we described an efficient and economical synthetic route leading to N-phenyl substituted pyrazole and 1,3,4-oxadiazole derivatives. Retrosynthetic disconnective analysis showed that the N-phenyl substituted pyrazole can be obtained from chalcone, accessible from the respective aldehyde, and acetophenone. The disubstituted 1,3,4-oxadiazole can be constructed from the respective aldehyde, which originates from pyrrole-containing compound, and formyl chloride. Based on our retrosynthetic analysis, N-phenyl substituted pyrazole was obtained by cyclization of the respective chalcone with phenylhydrazine to give pyrazoline which was in turn converted into pyrazole by oxidative aromatization. Potassium carbonate and a catalytic amount of molecular iodine were used to oxidatively cyclize semicarbazones into 1,3,4-oxadiazoles in a transition metal-free process. Novel pyrazole and 1,3,4-oxadiazoles with potential biological activity are investigated as antituberculosis, anticonvulsant, antidiabetic, anticancer, and tyrosinase inhibitory agents.

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid

H5IO6, as an efficient reagent for the aromatization of tetrahydro-β-carbolines: total synthesis of norharman, harmane, harmine, kumujian-C, and orthoscuticellines B - Sabane, Jagjivan K.; Gaikwad, Sunil V.; Gajbhiye, Jayant M.; Kumar, Pradeep (ChemistrySelect, 2026)
A new method is reported for the synthesis of beta-carbolines and their derivatives using H5IO6 in DMSO solvent. The method is mild and efficient for oxidative decarboxylation and aromatization of tetrahydro beta-carbolines (TH beta C), resulting in good to excellent yields (70% to 88%) of beta-carbolines. This protocol has further been utilized for the synthesis of beta-carbolines based natural products, for examples, norharmane, harmane, harmine, Kumujian-C, and Orthoscuticellines A and B.
Keywords: aromatization; beta-carboline; H5IO6; Harmine; orthoscuticellines; Oxidative